Effects of 4 weeks of high-intensity interval training and ß-hydroxy-ß-methylbutyric free acid supplementation on the onset of neuromuscular fatigue - Miramonti, A. A.; Stout, J. R.; Fukuda, D. H.; Robinson IV, E. H.; Wang, R.; La Monica, M. B.; Hoffman, J. R. (The Journal of Strength and Conditioning Research, 2016)
This study investigated the effects of high-intensity interval training (HIIT) and ß-hydroxy-ß-methylbutyric free acid (HMB) supplementation on physical working capacity at the onset of neuromuscular fatigue threshold (PWCFT). Thirty-seven participants (22 men, 15 women; 22.8 ± 3.4 years) completed an incremental cycle ergometer test (graded exercise test [GXT]); electromyographic amplitude from the right vastus lateralis was recorded. Assessments occurred preceding (PRE) and after 4 weeks of supplementation (POST). Participants were randomly assigned to control (C, n = 9), placebo (P, n = 14), or supplementation (S, n = 14) groups. Both P and S completed 12 HIIT sessions, whereas C maintained normal diet and activity patterns. The PWCFT (W) was determined using the maximal perpendicular distance (DMAX) method. Electromyographic amplitude (µVrms) over time was used to generate a cubic regression. Onset of fatigue (TF) was the x-value of the point on the regression that was at DMAX from a line between the first and last data points. The PWCFT was estimated using TF and GXT power-output increments. The 2-way analysis of variance (ANOVA) (group × time) resulted in a significant interaction for PWCFT (F = 6.69, p = 0.004). Post hoc analysis with 1-way ANOVA resulted in no difference in PWCFT among groups at PRE (F = 0.87, p = 0.43); however, a difference in PWCFT was shown for POST (F = 5.46, p = 0.009). Post hoc analysis among POST values revealed significant differences between S and both P (p = 0.034) and C (p = 0.003). No differences (p = 0.226) were noted between P and C. Paired samples t-tests detected significant changes after HIIT for S (p < 0.001) and P (p = 0.016), but no change in C (p = 0.473). High-intensity interval training increased PWCFT, but HMB with HIIT was more effective than HIIT alone. Furthermore, it seems that adding HMB supplementation with HIIT in untrained men and women may further improve endurance performance measures.